Keefektifan Pengembangan Media Buku AJIB Untuk Meningkatkan Keterampilan Berbicara Siswa SD - Raden Roro Endang Kusripinah; Setya Yuwana; Hendratno (Elementary Teacher Education Program, Majalengka University, 2023)
The speaking ability of elementary school students is in the low category, so an appropriate media is needed using the AJIB Book (Illustrated Speech Jockey Tool). This study aims to determine the effectiveness of the development of AJIB book media (speech illustration jockey tool) to improve speaking skills in Indonesian language subject speech material in class VI elementary school. The type of research used is Research and Development (R&D) with the development model in this study the 4-D development model. The results of the Wilcoxon Signed Ranks test found that P 0.000 <0.05, this indicates that there is a difference in the effect between the pre and post tests. The conclusion obtained in this study is that it has proven effective in developing AJIB book media (speech illustration jockey tools to improve speaking skills in Indonesian language subject speech material in class VI elementary school.